A novel aceE mutation leading to a better growth profile and a higher l-serine production in a high-yield l-serine-producing Corynebacterium glutamicum strain. (1st September 2016) - Guo, Wen; Chen, Ziwei; Zhang, Xiaomei; Xu, Guoqiang; Zhang, Xiaojuan; Shi, Jinsong; Xu, Zhenghong
Abstract: A comparative genomic analysis was performed to study the genetic variations between the l -serine-producing strain Corynebacterium glutamicum SYPS-062 and the mutant strain SYPS-062-33a, which was derived from SYPS-062 by random mutagenesis with enhanced l -serine production. Some variant genes between the two strains were reversely mutated or deleted in the genome of SYPS-062-33a to verify the influences of the gene mutations introduced by random mutagenesis. It was found that a His-594 → Tyr mutation in aceE was responsible for the more accumulation of by-products, such as l -alanine and l -valine, in SYPS-062-33a. Furthermore, the influence of this point mutation on the l -serine production was investigated, and the results suggested that this point mutation led to a better growth profile and a higher l -serine production in the high-yield strain 33a∆SSAAI, which was derived from SYPS-062-33a by metabolic engineering with the highest l -serine production to date.